Drug therapy for the elderly - Wehling, Martin (Springer, 2013)
With people aged 65 years and older currently making up the fastest growing age group throughout the world, the demographic revolution of an aging society will inevitably lead to increased pressure to develop a rationalistic and age-tailored process of diagnosis and treatment among the elderly. As aging people often suffer from several chronic diseases and are being treated with multiple medications concurrently, unwanted drug interactions occur more frequently. Whereas recent approaches have recommended to remove particular drugs from the medication regimen to avoid adverse effects, Drug Therapy for the Elderly underlines both indispensable and dispensable elements of drug treatment in order to provide an overall assessment of drugs suitable for the aged. In view of the multimorbidity and polypharmacy situations experienced by elderly patients, this book takes into account the special needs and requirements shown by this group, thus serving as a timely reference for physicians who treat the elderly.
Description based upon print version of record
Keywords: Alter; Pharmakotherapie